THE ATTITUDES TOWARD SPORT ADVERTISING AMONG THE QUESTION HOW OFTEN CONSUMERS PARTICIPATE IN SPORTS ACTIVITIES - Stevo Popović; Slavko Molna; Dragan Radovanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
This research was aimed at gaining relevant knowledge about the attitudes toward sport advertising among the question how often consumers participate in sports activities The sample included 433 respondents, divided into six subsample groups: consumers who do not participate in sport activities at all, then consumers who participate in sport activities less than ones a month, next 1-4 a month, 5-10 a month, 11-20 a month, as well as consumers participate in sport activities more than 20 times a months. The sample of variables contained the system of three general attitudes which were modeled by seven-point Likert scale. The results of the measuring were analyzed by multivariate analysis (MANOVA) and univariate analysis (ANOVA) and Post Hoc test. Based on the results it was concluded that significant differences occur at multivariate level, as well as between all three variables at a significance level of p=.05. It is interesting to highlight that it was found that the significant differences showed up between the consumers who participate in sports activities less than four times a months with negative attitudes and consumers who participate in sports activities more than five times a months with positive attitudes toward sport advertising